2008
DOI: 10.1099/jmm.0.2008/000968-0
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Scottish clinical isolates of Staphylococcus aureus

Abstract: The biofilm-forming capacity of 972 clinical isolates of Staphylococcus aureus was tested using a high-throughput polystyrene 96-peg plate format. Isolates of S. aureus were collected from patients in hospitals throughout Scotland from 2004 to 2006; 763 of these were meticillinresistant S. aureus (MRSA) and 209 were meticillin-sensitive S. aureus (MSSA). The biomass of each biofilm was quantified using a crystal violet staining technique. Isolates were divided into those that formed fully established biofilms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
75
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 25 publications
(26 reference statements)
9
75
4
2
Order By: Relevance
“…In this study, methicillin resistant isolates harbored higher rate of icaADBC genes compared to MSSA, but no significant difference was confirmed, similar to two other studies (27,28). Moreover, Smith determined no significant relation between susceptibility to methicillin and biofilm formation (29). Likewise, Rasha detected the icaAD genes in 32% of blood and catheter isolates (37 (35).…”
Section: Discussionsupporting
confidence: 74%
“…In this study, methicillin resistant isolates harbored higher rate of icaADBC genes compared to MSSA, but no significant difference was confirmed, similar to two other studies (27,28). Moreover, Smith determined no significant relation between susceptibility to methicillin and biofilm formation (29). Likewise, Rasha detected the icaAD genes in 32% of blood and catheter isolates (37 (35).…”
Section: Discussionsupporting
confidence: 74%
“…(Kwon et al, 2008). Other studies showed no difference in biofilm formation between MRSA and MSSA isolates (Smith et al, 2008;Indrawattana et al, 2013). In our study there was also no difference in biofilm formation between MRSA and MSSA isolates, although the mean optical density for MSSA was higher.…”
Section: Discussioncontrasting
confidence: 46%
“…Isolates from blood cultures showed a higher frequency of biofilm formation compared to isolates from other sites (Kwon et al, 2008). In the study by Smith et al, the isolates derived from skin had a greater ability to form fully established biofilms (Smith et al, 2008). In our study, the source of bacteraemia as established by clinical data for S. aureus blood-stream infections was not a predictor of biofilm formation.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…There are few studies in the literature about the biofilm production of staphylococci isolates recovered from hospital environments. Smith et al [22] studied MRSA isolates from a hospital and found that 25.7% were low biofilm producers, 53.8% were moderate and 20.5% were biofilm producers. In the same study, compared to MSSA isolates, 28.5% were non-biofilm producers, 43.5% were moderate and 28.0% were biofilm producers.…”
Section: Discussionmentioning
confidence: 99%